Resistance Exercise Training does not Affect Plasma Irisin Levels of Hemodialysis Patients - Moraes, C.; Leal, V. O.; Marinho, S. M.; Barroso, S. G.; Rocha, G. S.; Boaventura, G. T.; Mafra, D. (Hormone and Metabolic Research, 2013)
Irisin, a hormone secreted by myocytes induced in exercise, acts as a muscle-derived energy-expenditure signal that binds to undetermined receptors on the white adipose tissue surface, stimulating its browning and uncoupling protein 1 (UCP1) expression. The purpose of this study was to assess the effect of an intradialytic resistance exercise training program (RETP) on plasma irisin levels of hemodialysis (HD) patients and compare the baseline plasma irisin levels of HD patients to healthy subjects. This longitudinal study enrolled 26 patients undergoing HD (50% men, 44.8±14.1 years, body mass index (BMI) 23.5±3.9 kg/m2). The healthy subjects group consisted of 11 women and 7 men with mean age of 50.9±6.6 years and BMI, 24.2±2.7 kg/m2. Anthropometric and biochemistry parameters (Irisin by Enzyme-Linked Immunosorbent Assay) were measured at the baseline and after 6 months of RETP (in both lower limbs). There was no difference regarding gender, age, and BMI between HD patients and healthy subjects. Plasma irisin levels in HD patients were lower than in healthy subjects (71.0±41.6 vs. 101.3±12.5 ng/ml, p<0.05). Although the muscle mass increased in consequence of exercise [evaluated by arm muscle area from 27.9 (24.1) to 33.1 (19.0) cm2], plasma irisin did not differ significantly after exercises (71.0±41.6 vs. 73.3±36.0 ng/ml). HD patients seem to have lower plasma irisin when compared to healthy subjects. Moreover, a resistance exercise training program was unable to augment plasma irisin despite increasing muscle mass.
Keywords: chronic kidney disease; muscle mass; physical exercise; hormone